Pembinaan bagi Narapidana Hukuman Mati pada Rutan Kelas I Tanjungpinang - Hariyanto Saputra, Pogy; Subroto, Mitro (STISIPOL Raja Haji, 2023)
The death penalty is one of the punishments that is still applied and enforced in Indonesia, this is stated in the provisions of the Criminal Code. The prisoners/convicts are given guidance in prisons with the aim of achieving social reintegration or restoring the unity of the relationship between Prisoners and the community. The problem that arises is related to the development of death row convicts that they will no longer have the opportunity to correct their mistakes or behavior in social life, because it is certain that they will no longer interact socially with society. The purpose of this research is to find out the training for death row convicts in its implementation. The method used in this research is a qualitative research method. data sources used are primary data and secondary data. The results of this study are that the development of death row convicts is not much different from other convicts who are in prison. The absence of laws and regulations that clearly regulate the waiting period for the execution of death row convicts has resulted in the coaching carried out for death row convicts at the Tanjungpinang Class I State Detention Center carried out in accordance with the Law of the Republic of Indonesia Number 12 of 1995 concerning Corrections and the Decree of the Minister of Justice of the Republic of Indonesia. 1990 concerning Patterns of Development of Convicts / Prisoners. Death row convicts participate in coaching like other convicts so they don't feel pressured and stressed, in the form of personality development which includes mental and spiritual development, and physical development. and also in the form of fostering self-sufficiency through skills programs both independent business, small industrial business, industrial or agricultural activities to suit each talent.